Epidemiological characteristics of injury mortality in Guangdong Province, China, 2015 - Ruilin Meng; Xiaojun Xu; Yanjun Xu; Chao Luo; Haofeng Xu; Ye Wang; Xiuling Song; Liang Xia; Ni Xiao; Shaoen Zhou; Lifeng Lin (BMC, 2019)
Abstract Background As the fourth leading cause of death, injury is an important public health concern in Guangdong Province, China. The epidemiological characteristics of injury mortality is changing along with the social development. This study described the epidemiological characteristics of injury mortality in Guangdong Province by analyzing the death surveillance data in a few areas in Guangdong Province in 2015. Methods Using the mortality data from the Disease Surveillance Points (DSP) system, injury deaths were classified according to the International Classification of Disease-10th Revision (ICD-10). The data were stratified by areas (urban/rural), gender, age groups, injury types, and then overall and type-specific injury mortality rates were estimated for the whole Guangdong Province, China. Results We estimated that about 38,200 individuals died from injury in Guangdong Province in 2015, producing a mortality rate of 43.11/100,000. The overall age-standardized injury mortality in men was higher in rural areas compared with urban areas (41.29/100,000 versus 24.89/100,000). In terms of injury intent, unintentional injuries were the commonnest injury type, which accounted for 83.93% of the overall injury deaths, however, the deaths caused by suicide should not be ignored, which occupied 12.67% of the total injury deaths. In terms of injury cause type, falls, road-traffic accidents, suicide, drowning, and accidental poisoning were the top five leading types of injury deaths. Conclusions In Guangdong Province, injury is an important cause of death. Road-traffic accidents, falls, suicide, drowning, and accidental poisoning should be the priorities of intervention. Moreover, in rural areas, the men were the most targeted subpopulation of the prevention activities.